Yin Yang 1 extends the Myc-related transcription factors network in embryonic stem cells - Vella, Pietro; Barozzi, Iros; Cuomo, Alessandro; Bonaldi, Tiziana; Pasini, Diego (Nucleic acids research, 2012)
The Yin Yang 1 (YY1) transcription factor is a master regulator of development, essential for early embryogenesis and adult tissues formation. YY1 is the mammalian orthologue of Pleiohomeotic, one of the transcription factors that binds Polycomb DNA response elements in Drosophila melanogaster and mediates Polycomb group proteins (PcG) recruitment to DNA. Despite several publications pointing at YY1 having a similar role in mammalians, others showed features of YY1 that are not compatible with PcG functions. Here, we show that, in mouse Embryonic Stem (ES) cells, YY1 has genome-wide PcG-independent activities while it is still stably associated with the INO80 chromatin-remodeling complex, as well as with novel RNA helicase activities. YY1 binds chromatin in close proximity of the transcription start site of highly expressed genes. Loss of YY1 functions preferentially led to a down-regulation of target genes expression, as well as to an up-regulation of several small non-coding RNAs, suggesting a role for YY1 in regulating small RNA biogenesis. Finally, we found that YY1 is a novel player of Myc-related transcription factors and that its coordinated binding at promoters potentiates gene expression, proposing YY1 as an active component of the Myc transcription network that links ES to cancer cells.